Downstream Processing Strategies for Lignin‐First Biorefinery. Issue 19 (9th September 2020) - Sun, Zhuohua; Cheng, Jinling; Wang, Dingsheng; Yuan, Tong‐Qi; Song, Guoyong; Barta, Katalin
Abstract : The Cover Feature shows a smart lignin‐first biorefinery strategy and its contribution to create a more sustainable planet. In this strategy, upstream processing steps generate various lignin monomers with high yields, which then drive the downstream processing steps to produce more value‐added chemicals, fuels, and materials in a sustainable way. More information can be found in the Review by Z. Sun et al .